Venice anti-flood gates could wreck lagoon ecosystem. (6th December 2018) - Del Bello, Lou
Instead, researchers suggest injecting fluid cement or water below ground to lift the entire city. Instead, researchers suggest injecting fluid cement or water below ground to lift the entire city. Tourists in colourful waterproofs walk across an emergency wooden boardwalk in St. Mark's Square in Venice to avoid floodwater